Sustainable plastics : environmental assessments of biobased, biodegradable, and recycled plastics - Greene, Joseph P., 1961- (Hoboken, New Jersey : John Wiley and Sons, Inc, 2014)
"Providing guidelines for implementing sustainable practices for traditional petroleum based plastics, biobased plastics, and recycled plastics, Sustainable Plastics and the Environment explains what sustainable plastics are, why sustainable plastics are needed, which sustainable plastics to use, and how manufacturing companies can integrate them into their manufacturing operations. A vital resource for practitioners, scientists, researchers, and students, the text includes impacts of plastics including Life Cycle Assessments (LCA) and sustainability strategies related to biobased plastics and petroleum based plastics as well as end-of-life options for petroleum and biobased plastics"--
"A vital resource for practitioners, scientists, researchers, and students, the text includes impacts of plastics including Life Cycle Assessments (LCA) and sustainability strategies related to biobased plastics and petroleum based plastics as well as end-of-life options for petroleum and biobased plastics"--
C.2. Injection Stretch Blow Molding -- References -- Appendix D Industrial Compost Biodegradation Testing -- D.1. Methodology -- D.2. Materials -- D.3. Carbon Content Testing Results -- D.4. Biodegradation Results -- D.5. Phytotoxicity Testing -- D.6. Regulated Heavy Metal Testing -- References -- Appendix E Marine Biodegradation Testing -- E.1. Methodology -- E.2. Materials -- E.3. Experimental Setup -- E.4. Marine Biodegradation Results -- Appendix F Answers to Selected Questions at the End of Each Chapter.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Biodegradable plastics; Plastics -- Recycling; Plastics -- Environmental aspects; Green chemistry; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Biodegradable plastics; Green chemistry; Plastics -- Environmental aspects; Plastics -- Recycling; Electronic books; Electronic books